Key foundations for high-quality corporate reporting : international audit and assurance requirements and good practices in their implementation (UN New YorkUS, 2015)
Presents an overview of trends in the development and implementation of the International Standards on Auditing, as well as the related implementation challenges of such standards pertaining to regulatory, institutional and human capacity requirements.
Keywords: ACCOUNTING